Tinjauan Hukum Mengenai Tindak Pidana Perdagangan Orang - Akhirudin; Ariawan Gunadi (CV Rewang Rencang, 2024)
This study aims to examine the criminal act of human trafficking from the perspective of Indonesia’s positive law and its impacts on victims and society. The research method used is normative juridical with descriptive analysis of statutory regulations and legal doctrines. Law No. 21 of 2007 serves as the legal foundation for combating human trafficking, covering recruitment to exploitation through various criminal modes. Human trafficking causes severe social, economic, and psychological impacts, from deep trauma to social exclusion of victims. The state has established a comprehensive protection system, including rights recovery and international cooperation mechanisms. Despite existing regulations, challenges remain in enforcement and limited rehabilitation facilities. Therefore, effective TPPO eradication strategies require synergy between the government, civil society, and international actors to achieve substantive justice and comprehensive protection. In conclusion, addressing human trafficking must be holistic, with strengthened legal enforcement, victim protection, and sustainable public participation.